PENGARUH KOMUNIKASI PEMASARAN VIA TV COMMERCE DAN IKLAN RADIO TERHADAP KEPUTUSAN PEMBELIAN PRODUK DI OLX - Cahyani, Leni; Hidayat, Agus maolana (EDUTECH CONSULTANT, 2018)
This study aims to determine the role of marketing communications through TV Commerce and radio advertising in influencing the decision to purchase products in OLX. Marketing communications undertaken at OLX are expected for sellers to increase their sales, but for consumers it is rational to benefit from the offer of the product. In this study used 100 samples of consumers who have made purchases of products in OLX located in Bandung. Sampling is random (simple random sampling) through the spreading of questionnaires and interviews. The research variables consist of independent variable that is marketing communication through TV Commerce (X1) and radio advertisement (X2), while the dependent variable is Purchase Decision (Y). Discussion of this research by using descriptive analysis with path (Path Analysis), where the first tested data such as: test the normality, validity and reliability. The results showed that marketing communications in delivering messages and information through TV Commerce and radio advertisements conducted OLX provide positive consumer perceptions for purchasing decisions. But TV commerce has a greater impact than radio advertising. This is because the television media is an ideal medium to advertise mass consumption products and wide range power, and creative visualization is able to get the attraction yntuk buy products from the advertisement. Therefore, the products that exist in OLX will be more known to the public.